Optical Examination of Shockwave Propagation Induced by an Underwater Wire Explosion - Higa, O; Yasuda, A; Higa, Y; Shimojima, K; Hokamoto, K; Itoh, S (The International Journal of Multiphysics, 2016)
We have been investigating underwater-explosion-induced shockwave-propagation phenomena for use in a robust food-processing system. This system comprises a high-voltage capacitor bank with gap switch, water tank, and wire explosive. We carried-out optical observation of the shockwave generated by a wire explosion using electrical discharge in the water tank. Simultaneously, we measured the shock pressure and investigated the effects of various electrical characteristics upon the shockwave-propagation phenomena. To obtain various strengths of the underwater shockwave, 0.6-, 1.0-, and 1.4-mm-wide wires made from 1.0-mm-thick aluminum plates were used at various voltages. As an example, a shockwave having a propagation velocity of 1,600 m/s was observed using the explosion of the 1.0-mm-wide aluminum wire. We found that the strength of the shockwave could be well-controlled by the discharge voltage and wire size.